Will Robie : The Guilty - Book 5 - Baldacci, David; Brewer, Kyf; Cassidy, Orlagh (New York : Hachette Audio, 2015)
Will Robie is the government's most professional, disciplined, and lethal assassin. He infiltrates the most hostile countries in the world, defeats our enemies' advanced security measures, and eliminates threats before they ever reach our shores. But now, his skills have left him. Sent overseas on a critical assignment, he fails, unable to pull the trigger. Absent his talents, Robie is a man without a mission, and without a purpose. To recover what he has lost, Robie must confront what he has tried to forget for over twenty years: his own past.
Keywords: Assassins -- Fiction; Suspense fiction; Audiobooks